(untitled) (Bangladesh Journal of Zoology, 2023)
Extracts of Polygonum hydropiper leaves in Methanol was introduced to the 3rd and 4th instar larvae of Aedes aegypti with various concentration (.25–1.5 μg/ml). Insecticidal assays data showed significant mortality against the Aedes aegypti larvae. The LC50 and LC90 value after 24 hours of exposure was 0.002 and 0.47 μg/ml respectively. As predicted the result showed that the larvicidal activity of P. hydropiper on Ae. aegypti larvae was dose reliant. The result clearly exhibited that methanol extract of P. hydropiper, as a potential biological control agent against Ae. aegypti larvae, is eminent. Bangladesh J. Zool. 51(1): 119-127, 2023